The Effect Of Distributed Generation (DG) Placement On Electricity Reliability - Agung Nugroho; Ajub Ajulian ZM; Bambang Winardi (YCMM, 2023)
The continuity of the supply of electric power is becoming a greater demand from consumers. Feeder MRA05 GI Mrica Banjarnegara supplies electrical energy for parts of Banjarnegara Regency until 2020 has 4 distributed generations, namely PLTMH Sigebang 500 KW, PLTMH Kincang 320 KW, PLTMH Adipasir 320 KW, PLTMH Rakit 500 KW. Based on recorded data in 2020, the MRA05 feeder experienced 15 blackouts/year, with a total outage duration of 38.68 hours/year, of course it was enough to disrupt the continuity of the distribution of electrical energy to consumers. This research discusses the magnitude of the reliability index (SAIFI, SAIDI, CAIDI) when the DG is not installed and installed. The calculation of the magnitude of the reliability index was carried out using the Reliability Index Assessment (RIA) method, the calculation results were compared with the results of the ETAP 12.6.0 software simulation. The reliability index is based on the RIA method when DG is not installed, the SAIFI value is 2.96228 interruptions/year, the SAIDI value is 9.1185 hours/year, the CAIDI value is 3.078 hours/interruption, When DG is installed, the SAIFI value is 2.96228 disturbances/ year, the SAIDI value is 7.567 hours/year, the CAIDI value is 2.5546 hours/interruption.